Partial collusion with asymmetric cross-price effects - Luca Savorelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
Asymmetries in cross-price elasticities have been demonstrated by several empirical studies. In this paper we study from a theoretical stance how introducing asymmetry in the substitution effects influences the sustainability of collusion. We characterize the equilibrium of a linear Cournot duopoly with substitute goods, and consider substitution effects which are asymmetric in magnitude. Within this framework, we study partial collusion using Friedman (1971) solution concept. Our main result shows that the interval of quantities supporting collusion in the asymmetric setting is always smaller than the interval in the symmetric benchmark. Thus, the asymmetry in the substitution effects makes collusion more difficult to sustain. This implies that previous Antitrust decisions could be reversed by considering the role of this kind of asymmetry.
Keywords: C72; D43; L13; 330